Relationship between health information literacy and health promoting lifestyle among first-degree relatives of patients with colorectal cancer in China: the mediating effect of health belief - Jingru Zhou; Jingru Zhou; Li Zhao; Yanjun Liu; Lin He; Fang Yang; Haichao Wang; Jing Fan; Qianer Li; Sisi Guo; Yanfen Wang; Yan Liu; et al. (Frontiers Media S.A., 2023)
BackgroundHistory of first-degree relatives with colorectal cancer is one of the most important and common risk factors for colorectal cancer in China. Most chronic diseases, such as malignancies, are preventable by adopting health-promoting behaviors and other approaches. However, the relationships among factors affecting the health-promoting lifestyles of first-degree relatives with colorectal cancer have not been sufficiently studied. This study aimed to test the mediation effects of Health belief in the relationship between health-promoting lifestyle and health information literacy among first-degree relatives with colorectal cancer.MethodsA cross-sectional descriptive design was conducted using convenience sampling of 856 first-degree relatives of CRC patients attending three tertiary care hospitals in Nanchong and Deyang of China from December 2020 to December 2022. Questionnaires were used to collect data on the participants' demographic information, the colorectal cancer health beliefs, the health promotion lifestyle, and the health information literacy. Data were analyzed with descriptive statistics, one-way ANOVA, Pearson's correlation coefficients, and mediation analysis using SPSS 25.0 program and its macro-program PROCESS.ResultsThe findings indicated health information literacy was less, health belief was at the medium level, and performance of health promotion behavior was average for first-degree relatives of colorectal cancer. Whereas first-degree relatives of colorectal cancer health-promotion lifestyle had a positive correlation with health beliefs (r = 0.376, p < 0.01) and health information literacy (r = 0.533, p < 0.01), health beliefs had a positive correlation with health information literacy (r = 0.337, p < 0.01). Health beliefs mediated the positive effect of health information literacy on health-promoting lifestyles (β =0.420, 95% CI, 0.288-0.581), and indirect effects accounted for 14.0% of the total effect.ConclusionHealth information literacy and health beliefs are key factors associated with a health-promoting lifestyle among first-degree relatives with colorectal cancer. These factors have direct and indirect effects on each other and on health-promoting lifestyles. To enhance health-promoting lifestyles among first-degree relatives with colorectal cancer, interventions that strengthen health beliefs and provide health information literacy should be developed.